Konzervek hőkezelésének költségcsökkentése gyártásprogramozással - Fabulya, Zoltán (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
Examination of the load-efficiency graph of the boiler showed that gas fee which determines the direct expenses significantly can be reduced by 6% if the load is balanced. It is typical to the present practice that when different products of different load are made at the same time, it is not taken into consideration when the shifts are planned. Then, for example, instead of the average load of 50% per shift it is typical that even the average load of 30% and of 70% can be observed in the consecutive shifts. However, even within one shift great deviations can be experienced because the production is not scheduled. It can be seen from the results that the increase of the unbalanced feature of the load results in the growth of the loss. With smaller average loads, balancing the load is of a bigger importance since the relative loss can be even 6% then. Besides the load of 50%, which can be regarded as the annual average, almost the loss of 5% was experienced in the worst case.